Dynamique de formation sur le lieu de travail : paroles de formateurs - André Balleux (Perspectives Interdisciplinaires sur le Travail et la Santé)
By drawing up a picture of the skills developed by trainers while accompanying their apprentices, the author seeks to portray and size their working universe. Trainers and apprentices are the fragile actors in a training method as old as the trade charters but as modern as cooperative education, and receive little recognition for their efforts. This text invites readers to discover the human side of the singular relationship between master and apprentice, where the expertise conveyed is not only that of the trade, but also that developed by the expert himself.